Geographical Information and Planning European Perspectives - Stillwell, John 1952-; Geertman, Stan 1955-; Openshaw, Stan 1946- (Advances in Spatial Science, The Regional Science Series, 1999)
The 1990s have seen some remarkable changes in geographical information (GI) provision and computer technology that have impacted on many of the activities that constitute planning in all its different forms. However, relatively few texts in the field of geographical information systems (GIS) and planning have been published since Henk Scholten and John Stillwell edited Geographical Information Systems for Urban and Regional Planning in 1990. This volume seeks to redress the balance by showing how GI of various types is being used in urban, physical, environmental, socio-economic and business planning contexts at local, regional and national scales with the assistance of GIS and modelling methods, and how the uses of GI and GI technologies have evolved over the last decade. During this period, a number of meetings took place in Europe in different locations organised initially by European Geographical Information Systems (EGIS, 1990- 94) and more recently by the Joint European Conference and Exhibition (JEC) on Geographical Information (1995-97). These meetings brought together members of the GI community from across the world to discuss GI research and GIS applications. One of the Special Interest Groups associated with the JEC gatherings was that on 'Geographical Information and Planning' and several of the contributions in this book have their origins in papers presented to the group's meetings